2000
DOI: 10.1109/36.885209
|View full text |Cite
|
Sign up to set email alerts
|

A novel signal processing technique for clutter reduction in GPR measurements of small, shallow land mines

Abstract: In this paper, a signal processing technique is developed to reduce clutter due to ground bounce in ground penetrating radar (GPR) measurements. This technique is especially useful when a GPR is used to detect subsurface antipersonnel mines. The GPR clutter is modeled using a simple parametric model. Buried mine and clutter contributions are separated through a pair of coupled iterative procedures. The algorithm outperforms existing clutter reduction approaches and also yields target features that are useful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Conventional GPR radar processing includes several key steps: first a range dependent gain called "gain recovery" is applied to equalize the added loss from penetrating deeper into the ground or snowpack [29], [30]. This is typically followed by position offset correction [31], [32], [33] that accommodates the air gap between the antenna and ground surface. Offsets are typically not an issue for snow sensing as we are only interested in the snow depth (top air-snow interface relative to bottom snow-ground interface), not the snow's position relative to the UAV.…”
Section: Campaign and Airborne Snow Resultsmentioning
confidence: 99%
“…Conventional GPR radar processing includes several key steps: first a range dependent gain called "gain recovery" is applied to equalize the added loss from penetrating deeper into the ground or snowpack [29], [30]. This is typically followed by position offset correction [31], [32], [33] that accommodates the air gap between the antenna and ground surface. Offsets are typically not an issue for snow sensing as we are only interested in the snow depth (top air-snow interface relative to bottom snow-ground interface), not the snow's position relative to the UAV.…”
Section: Campaign and Airborne Snow Resultsmentioning
confidence: 99%
“…In [9], a time-gating approach is suggested, that reduces the early part of the signal to zero, but has the drawback that it might also remove target responses, especially when shallow buried objects are present. Another background removal method, using frequency domain basis functions to represent clutter and target signal, is presented in [10]. Filtering in the frequencywavenumber (f-k) domain over a window of the GPR data has also been employed for the removal of the direct air wave [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is used to detect elastic waves with buried landmines [13]. By developing a signal processing technique for Ground Effect Radar (GPR) measurements, this technique has shown positive results, especially when using a Ground Effect Radar (GPR) to detect underground anti-personnel mines [14]. It has been demonstrated that these algorithms provide a significant classification performance gain by examining using a broadband frequency field EMI sensor and developing an algorithm [15].…”
Section: Introductionmentioning
confidence: 99%